2014
DOI: 10.19173/irrodl.v15i1.1638
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of effective online learning: Assessing satisfaction levels of graduate students of mathematics education associated with human and design factors of an online course

Abstract: This exploratory research project investigated graduate students' satisfaction levels with online learning associated with human (professor/instructor and instructional associate) and design factors (course structure and technical aspects) using a survey study. A total of 81 graduate students (master's students who majored in math and science education) enrolled in an online math methods course (Conceptual Geometry) participated in this study. According to the results of this study, student satisfaction level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(101 citation statements)
references
References 20 publications
3
87
0
11
Order By: Relevance
“…The results are presented in Tables 1 and 2. Lee (2014) and Ku, Akarasriworn, Glassmeyer, Mendoza, and Rice (2011) which indicated that students pay more attention when the online course materials are presented with clear guidelines and expectations. Item 8 with (p<.05) shows how determined and resilient the students are in learning in this mode.…”
Section: Resultsmentioning
confidence: 99%
“…The results are presented in Tables 1 and 2. Lee (2014) and Ku, Akarasriworn, Glassmeyer, Mendoza, and Rice (2011) which indicated that students pay more attention when the online course materials are presented with clear guidelines and expectations. Item 8 with (p<.05) shows how determined and resilient the students are in learning in this mode.…”
Section: Resultsmentioning
confidence: 99%
“…Several preceding studies were consulted (Feldstein et al, 2012;Hilton et al, 2013;Bliss et al, 2013;Affordable Learning Georgia, 2015) that asked similar questions in students surveys. Additionally, the OER Research Hub's shared list of survey questions, and some online learning literature focusing on usability and instructional design (Young & Hoerig, 2013;Lee, 2014) were also consulted for additional guidance on survey items. Paper surveys were distributed to students at the end of each class section.…”
Section: Methodsmentioning
confidence: 99%
“…In a similar study [18] investigated graduate students' satisfaction levels with online learning associated with human (professor/instructor and instructional associate) and design factors (course structure and technical aspects) using a survey study. A total of 81 graduate master's students who majored in math and science education enrolled in an online math methods course (Conceptual Geometry) participated in this study.…”
Section: Blended Learning and Higher Education Students' Satisfacmentioning
confidence: 99%